Characterizing nanoparticles in complex biological media and physiological fluids with depolarized dynamic light scattering. Issue 14 (29th January 2015) - Balog, S.; Rodriguez-Lorenzo, L.; Monnier, C. A.; Obiols-Rabasa, M.; Rothen-Rutishauser, B.; Schurtenberger, P.; Petri-Fink, A.
Abstract : Characterization of NPs in physiological and biological fluids is challenging, yet can be met by using depolarized scattering, offering advantages over UV-Vis and fluorescence correlation spectroscopy. Abstract : Light scattering is one of the few techniques available to adequately characterize suspended nanoparticles (NPs) in real time and in situ . However, when it comes to NPs in multicomponent and optically complex aqueous matrices – such as biological media and physiological fluids – light scattering suffers from lack of selectivity, as distinguishing the relevant optical signals from the irrelevant ones is very challenging. We meet this challenge by building on depolarized scattering: Unwanted signals from the matrix are completely suppressed. This approach yields information with an unprecedented signal-to-noise ratio in favour of the NPs and NP-biomolecule corona complexes, which in turn opens the frontier to scattering-based studies addressing the behaviour of NPs in complex physiological/biological fluids.